Technology and Conference Interpreting: an introduction to the use of instant messaging apps - Adams, Heather (Technium Social Sciences Journal, 2021)
This article presents the use of well-known instant messaging apps in conventional conference interpreting situations, as a tool to enhance real-time communication between a team of interpreters, thereby improving coordination before, during and after an assignment, and enabling the interpreters to present a highly professional image to event organizers and delegates.